THE EFFECT OF SUBSTITUTING SAPU-SAPU FISH MEAL WITH LOCAL FISH MEAL ON THE GROWTH OF TILAPIA - Sulaeman, Muhammad Anugrah; Surianti, Surianti; Damis, Damis (Universitas Mataram, 2025)
Tilapia in Sidenreng Rappang Regency has the potential to be cultivated, because it is popular in the community. However, there is a problem in tilapia production, namely the high cost of feed. Raw materials for feed are one of the causes of the high price of feed, So an alternative is needed to use local raw materials that are cheap and easy to obtain, namely using broomstick fish meal. This study aims to determine the effect of increasing tilapia production through substitution of fish meal with catfish meal in artificial feed on nutritional quality, growth rate, feed consumption level, and hepatosomatic index. This study was conducted in January - February 2025. Located at the Unhas Education Pond, Bojo District, Barru Regency, South Sulawesi Province. This research used a completely randomized design (CRD) with 5 treatments and 3 replications, so that there were 15 research containers filled with 15 individuals per container weighing 3 grams. The treatments given were treatment A = 100% local flour and 0% broom-sapu fish meal, treatment B = 75% local fish meal and 25% broom-sapu fish meal, treatment C = 50% local flour and 50% broom-sapu fish meal, treatment D = 25% local fish meal, 75% broom-sapu fish meal, treatment E = 0% local fish meal, 100% broom-sapu fish meal. Data were analyzed using a comparison of the mean analysis of variance (ANOVA). Based on the results of the study, the treatment with the best value in the proximate analysis of feed, growth parameters and feed consumption was treatment E with a crude protein value of 32.81%, growth (3.810 ± 0.18a) and feed consumption value (13.23 ± 1.57a). In the Hepatosomatic Index parameter, the treatment with the highest value was treatment D with a value of (0.15 ± 0.00a).